Designing Strategy for Waste Management Business in Cement Company Using Scenario Planning - Arifianto, Arifianto; Sunitiyoso, Yos (Jurnal Indonesia Sosial Sains, 2025)
Economic and population growth in the future will increase waste generation and environmental challenges for the Indonesian Government. Cement plants can utilize waste as alternative fuel and raw materials, providing waste disposal services. This research discussed strategies for cement companies to develop their waste management business. Strategic tools called scenario planning are used in this research to create robust strategies facing future uncertainties. This research used a qualitative thematic data analysis from interviews with experts to identify critical uncertainties. The key focal issues are how will regulatory, market competition, and sustainability trends impact development of waste management business in cement company over the next 5 years. This research involved 6 industry experts from different companies, cement companies, government, and regulators. Through interviews and thematic data analysis, driving forces were identified and by using expert ratings, critical uncertainties were defined. The critical uncertainties are regulation and industry competition, which then shaped the four scenarios as the result. These scenarios have implications that impact the waste management industry and cement companies must be able to adapt to the emerging scenario. This research concludes with recommendations for cement company to leverage process efficiency in waste utilization, advocate to government and regulators, utilize branding as environmentally friendly solution to the waste problem, engage in research and development of waste processing technologies, establish strategic partnership with relevant stakeholder, and adjusting focus in terms of investment spending and technology adoption.